Uji Potensi Antifungi Perasan Daun Seledri (Apium graveolens L) Terhadap Aspergilllus terreus Secara In Vitro [Antifungal Potential Test Of Celery Leaves Juice (Apium graveolens L) Against Aspergilllus terreus By In Vitro] - Sudarno Sudarno; Illa Rohdiana Hermawati; Didik Handijatno (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Aspergillus terreus is a fungal that is able to produce several mycotoxins such as patulin, sitrinin and aflatoxin and contained in processed mackerel mixed with fresh steamed way. The impact of the use of chemicals to control fungal attack A. terreus showed a negative effect. This study aims to determine the potential and the minimum concentration of the juice of the leaves of celery (Apium graveolens L) as antifungal against the growth of A. terreus in vitro. The experiment was conducted at the Laboratory of the Faculty of Fisheries and Marine Airlangga University in July 2013. The method was used in this research that using paper disc diffusion method. Treatment outcome data were analyzed using descriptive statistics. Test potential antifungal celery juice in inhibiting the growth of fungus A. terreus obtained negative be results. The concentrations of juices were given as a treatment of 10 % to 100 % are not able to inhibit the growth of A. terreus shown with no inhibition zone formation in all treatments except the concentration of 10 % formalin as a control (+).